2016
DOI: 10.3233/nua-150054
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mastication on cognition: Evidence for intervention and the role of adult hippocampal neurogenesis

Abstract: Abstract. Adult hippocampal neurogenesis (AHN) in the dentate gyrus of the hippocampus has been shown to affect mood, cognition, learning ability and memory. A growing area of interest is whether mastication or chewing also affects AHN. This article aims to collect the evidence from animal and human studies to ascertain whether mastication is an oral environment enrichment capable of having a modulatory effect on AHN and associated behaviors.Current data point toward a causal relationship between masticatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) and its receptor, tyrosine kinase receptor B (TrkB; encoded by the Ntrk2 gene), promote neuronal cell proliferation, differentiation, survival, and synapse formation (Vicario-Abejón et al 2002;Lu 2003). Masticatory dysfunction downregulates the BDNF pathway, resulting in the reduction in the number of neuronal progenitor cells and functional neurons (Smith et al 2016). These together suggest the linkage between BDNF/TrkB signaling and masticatory dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) and its receptor, tyrosine kinase receptor B (TrkB; encoded by the Ntrk2 gene), promote neuronal cell proliferation, differentiation, survival, and synapse formation (Vicario-Abejón et al 2002;Lu 2003). Masticatory dysfunction downregulates the BDNF pathway, resulting in the reduction in the number of neuronal progenitor cells and functional neurons (Smith et al 2016). These together suggest the linkage between BDNF/TrkB signaling and masticatory dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the above, there are pathological changes in peridontal tissues and uncontrolled bone losses as well as destruction of temporomandibular joint structures, strain, and development of chewing muscles. This in turn does not remain without any influence on certain cognitive functions coordinated by certain brain structures [42]. Mediating function in this case is fulfilled by brain-derived neurotrophic factor (BDNF) as well as its receptor, TrkB, dysfunctions within chewing organ enhancing lowering of progenitor cells level (kind of stem cell used for regeneration process) and functional neurons as a result of action of BDNF tracts removal from adjustment [43].…”
Section: Psycho-neurophysiological Mechanisms In Chewing Organs Disormentioning
confidence: 99%
“…Epidemiologic studies have suggested associations between cognitive ability and oral conditions, such as number of teeth (Luo et al, 2015;Li et al, 2017;Oh et al, 2018) and dental occlusion (Ono et al, 2010;Franco et al, 2012;Takeuchi et al, 2015). Furthermore, occlusal force (Takeshita et al, 2016;Ikebe et al, 2018) and chewing ability have been shown to have effects on cognitive ability (Chen et al, 2015;Natalie et al, 2015;Seraj et al, 2017). Oral reconstruction by means of wearing a denture may induce cortical activation in prefrontal, sensorimotor, and sensory association cortices during chewing performance (Kimoto et al, 2011;Kamiya et al, 2016) and might also contribute to antiaging cognitive activation in the prefrontal cortex of elderly edentulous patients (Banu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%